التربية الإعلامية و إسهامات المدرسة في تفعيلها - بن عيسى, رابح (جامعة الوادي - University of Eloued, 2021)
لقد أدت الحاجة والضرورة لظهور التربية الإعلامية كخط دفاع للتصدي لوسائل الإعلام التي توغلت بشكل كبير و متزايد في جميع مجالات الحياة الاجتماعية، حيث أصبح من الصعب على الإنسان الذي لا يملك وعيا كافيا أن يتعرف على الخبر الصحيح أو المغرض و غير المغرض، نتيجة لتواجد كل هذا الزخم الكبير في المادة الإعلامية. وهذا ما دعا الحكومات و المنظمات إلى الاهتمام المتزايد بالتربية الإعلامية من خلال عقد المؤتمرات و الملتقيات، وهو الأمر الذي استدعى من الكثير من الدول أن تضع من بين أهم أولوياتها تعليم التربية الإعلامية بالمؤسسات المدرسية لما لهذه الأخيرة من آليات واستراتيجيات لمجابهة القوة الإعلامية الكبيرة و المتنامية، لذا سنتطرق في ورقتنا البحثية إلى مفهوم التربية الإعلامية و أهميتها و دورها، ودور المدرسة في تفعيل التربية الإعلامية في أوساط الناشئة. الكلمات المفتاحية: التربية الإعلامية؛ الإعلام التربوي؛ التربية الإعلامية المدرسية. Abstract: The need and necessity for media education to emerge as a line of defense has led to a response to the media, which has become increasingly and increasingly involved in all spheres of social life.It has become difficult for a human being who does not have enough awareness to know the right or the wrong, because of all the great momentum in the media.This has led governments and organizations to pay increased attention to media education through conferences and meetings.This has led many countries to place one of their top priorities on teaching media education in schools.Given the mechanisms and strategies of the latter to counter the great and growing media power.In our research paper, we will address the concept of media education, its importance and role, and the role of the school in promoting media education among young people. Keywords: Media education; educational media; School media education
Media education and the school's contribution to its functioning
مقال
Keywords: التربية الإعلامية؛ الإعلام التربوي؛ التربية الإعلامية المدرسية; Media education, educational media, School media education